Answer:
Step-by-step explanation:
[1] 3x - 4y = -24
[2] -x - 16y = -52
Graphic Representation of the Equations :
-4y + 3x = -24 -16y - x = -52
Solve by Substitution :
// Solve equation [2] for the variable x
[2] x = -16y + 52
// Plug this in for variable x in equation [1]
[1] 3•(-16y+52) - 4y = -24
[1] - 52y = -180
// Solve equation [1] for the variable y
[1] 52y = 180
[1] y = 45/13
// By now we know this much :
x = -16y+52
y = 45/13
// Use the y value to solve for x
x = -16(45/13)+52 = -44/13
Solution :
{x,y} = {-44/13,45/13}
8f³g-12f⁴g² = 4f³g (2 - 3fg)
Hope it helps
Answer:
x = -2
Step-by-step explanation:
The root will touch the axis and bounce off when the exponent is even. In that case, that means (x + 2)² is the binomial that will bounce. Therefore, the root which bounces and touches the x-axis is x = -2.
B subtract 18 from both sides
(1)
f(x) + g(x) = 3x + 2 + 2x + 5 = 5x + 7
f(x) - g(x) = 3x + 2 - 2x - 5 = x - 3
(2)
f(x) + g(x) = 4x - 1 + 3x - 4 = 7x - 5
f(x) - g(x) = 4x - 1 - 3x + 4 = x + 3
(3)
f(x) + g(x) = - 5x + 3 + 2x - 4 = - 3x - 1
f(x) - g(x) = - 5x + 3 - 2x + 4 = - 7x + 7
(4)
f(x) + g(x) = 3x - 4 - 2x + 3 = x - 1
f(x) - g(x) = 3x - 4 + 2x - 3 = 5x - 7
(5)
f(x) × g(x) = - 2(- x + 7 ) = 2x - 14
(6)
f(x) × g(x) = - 5(2x - 7) = - 10x + 35